Marketing strategies of Polish companies on foreign markets = Strategie marketingowe polskich firm na rynkach zagranicznych - Grzegorczyk, Wojciech (Zielona Góra: Faculty of Economics and Management Press)
In the years 2017-2018 the Marketing Faculty of Łódź University conducted a research project "Marketing strategies of companies based in Łódź Voivodeship on foreign markets". The aim of this text is to present the initial research findings strategies implemented by surveyed companies on foreign markets.
Keywords: marketing międzynarodowy; strategie marketingowe; rynki zagraniczne; international marketing; marketing strategies; foreign markets